LITERATURE REVIEW: PENGARUH PEMBERIAN KINESIO TAPING TERHADAP KEMAMPUAN MOBILITAS PADA PASIEN OSTEOARTRITHIS LUTUT - Siti Amira Fauziah; Muhammad Siddik; Didik Dwi Sanyoto; Bambang Dwi Putranto; Pagan Pambudi (Homeostasis, 2022)
Osteoarthritis (OA) is a degenerative disease in the elderly and attacks the joints and causes mobility problems. Kinesio taping therapy is an alternative treatment to minimize OA. This literature review aims to describe the effect of kinesio taping on mobility ability in knee osteoarthritis patients. The design of this research is Systematic Literature Reviews (SLR) which was obtained based on searching the sources of articles in English and Indonesian in the Public Medline, Science Direct, and Google Scholar databases. The article search criteria used in the literature review are articles that use English and Indonesian and are published in 2010-2021. Search articles in the literature review using the appropriate keywords consisting of kinesio taping, mobility, and knee osteoarthritis in order to obtain eight articles in literature journals. The results of a literature review showed that the administration of kinesio taping from 8 articles showed a significant effect on the mobility ability and range of motion of patients with knee osteoarthritis so as to increase mobility (p<0.05). This significant effect is indicated by a decrease in the time required for the timed up and go test (TUG).